The autonomic nervous system and ventricular arrhythmias in myocardial infarction and heart failure. Issue 2 (5th February 2020) - Wu, Perry; Vaseghi, Marmar
Abstract: Ventricular arrhythmias (VA) can range in presentation from asymptomatic to cardiac arrest and sudden cardiac death (SCD). Sustained ventricular tachycardias/ventricular fibrillation (VT/VF) are a common cause of SCD in the setting of myocardial infarction (MI) and heart failure. A particularly arrhythmogenic cardiac syncytia in these conditions can be attributed to both sympathetic activation and parasympathetic dysfunction, while appropriate neuromodulation has the potential to reduce occurrence of VT/VF. In this review, we outline the components of the autonomic nervous system that play an important role in normal cardiac electrophysiology and function. In addition, we discuss changes that occur in the setting of cardiac disease including adverse neural remodeling and neurohormonal activation which significantly contribute to propensity for VT/VF. Finally, we review neuromodulation strategies to mitigate VT/VF which predominantly rely on increasing parasympathetic drive and blockade of sympathetic neurotransmission.